English Speaking Varieties of English Instructors at Some English Courses in Makassar (A Case Study) - Merla Madjid (Athena: Journal of Social, Culture and Society, 2023)
Regional languages affect the way a person speaks English, for example in the aspect of pronunciation, especially for English teachers. This refers to the speaker seeing the difference between sound and speech. Buginese and Makassarese are tribes with strong accents. Therefore, this study aims to identify what things appear when speaking English from the influence of the Buginese language in an English course in Makassar City. This research adopts a qualitative case study. Data analysis was collected based on four phases, namely sample data collection, data presentation, data verification and data processing. This shows that teachers are usually influenced by regional languages when speaking English and in daily conversation. Qualitative research is to understand the meaning of the individual and the group environment.The results of the study show that the errors that often occur are the omission of elements in language such as grammar, conjunctions, etc. English teachers must know that their first language can affect their pronunciation when speaking English, and they must get used to getting used to good English pronunciation.